A Reliable Value Selection of Excitation Capacitance for a Self-Excited Induction Generator Operating Under Different Fault and Excitation Conditions - Hussein Kadhum, Hayder; Hamzah Abdullah, Alaa (Iraqi Journal for Electrical and Electronic Engineering, 2026)
Recently, researchers have focused their efforts to generate electricity on renewable energy sources. Wind power systems are considered good alternative sources of clean energy. Induction generators are the best choice for generating this energy due to their simplicity, robustness, and low maintenance requirements. However, their main drawback is their need for leading reactive power to build the terminal voltage and generate electrical power. This drawback can be overcome using a terminal capacitor across the generator terminals to generate this leading reactive power. This research focuses on: 1-Provides a methodology for selecting an accurate and reliable value of the excitation capacitance required for self-excited induction generators (SEIG), which can be used in pumps operating as turbines (PATs + SEIG). When operating at different speeds and loads. For these systems, the choice of capacitance for the SEIG is of utmost importance. 2- A simplified and understandable method derived from nodal analysis is presented for calculating the exact excitation capacitance of a self-excited induction generator (SEIG) under various conditions. 3-A new analysis and model of (SEIG) is presented. The proposed model consists of an induction generator, a self-excited capacitor, and a RL load. It is used to study the performance of SEIG under different faults and excitation (sudden short circuit, unbalanced excitation, sudden load surge, sudden disconnection of excitation capacitance, and load disturbance). Simulations are created using MATLAB-SIMULINK to validate the proposed model.